The Trinity : An Introduction - Swain, Scott R.; Cole, Graham A. (Graham Arthur), 1949-; Martin, Oren R. (Wheaton, Illinois : Crossway, 2020)
"Scott R. Swain examines the Trinity, presenting its biblical foundations, systematic-theological structure, and practical relevance for the church today"--
Includes bibliographical references and index.
Keywords: Trinity; Doctrine of Trinity